2006
DOI: 10.1007/s11010-006-9280-x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine induces inflammatory activation of human coronary artery smooth muscle cells

Abstract: Lysophosphatidylcholine (LPC) is the major bioactive lipid component of oxidized LDL, thought to be responsible for many of the inflammatory effects of oxidized LDL described in both inflammatory and endothelial cells. Inflammation-induced transformation of vascular smooth muscle cells from a contractile phenotype to a proliferative/secretory phenotype is a hallmark of the vascular remodeling that is characteristic of atherogenesis; however, the role of LPC in this process has not been fully described. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 35 publications
3
80
0
Order By: Relevance
“…More importantly, lyso-PC levels are increased during the oxidation of LDL ( 22 ). Oxidized LDL (OxLDL) is important in the generation of foam cells and is involved in many aspects of the pathogenesis of atherosclerosis, and as lyso-PC is the major bioactive lipid component of OxLDL ( 11,23 ), it has been suggested that lyso-PC is the major factor contributing to the proatherogenic potential of OxLDL (24)(25)(26).…”
Section: Oil Red O Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, lyso-PC levels are increased during the oxidation of LDL ( 22 ). Oxidized LDL (OxLDL) is important in the generation of foam cells and is involved in many aspects of the pathogenesis of atherosclerosis, and as lyso-PC is the major bioactive lipid component of OxLDL ( 11,23 ), it has been suggested that lyso-PC is the major factor contributing to the proatherogenic potential of OxLDL (24)(25)(26).…”
Section: Oil Red O Stainingmentioning
confidence: 99%
“…4). We found that there was an increased retention time on the test samples compared with the standards, also high levels of lyso-PC (18)(19)(20), and that lyso-PC is a major bioactive lipid component of OxLDL (24)(25)(26), we decided to test whether cholesterol or CE accumulation would have any effects on the metabolism of lyso-PC. To test this, we loaded THP-1 monocytes and macrophages with 14 C-lyso-PC alone, cholesterol/ 14 C-lyso-PC, and CE/ 14 C-lyso-PC micelles and incubated for 4 h and 24 h. Lipid and aqueous fractions were extracted from the cells and analyzed by TLC and autoradiography analysis.…”
Section: Monocytes and Macrophages Show A Different Pattern Of Cholinmentioning
confidence: 99%
“…Further, lyso-PC has also been found to stimulate the release of pro-inflammatory cytokines, such as IL-8 and IL-6, and of growth factors, such as bFGF, in human coronary artery SMCs [224]. Even nanomolar concentrations of lyso-PC are able to stimulate cytokine expression and monocyte recruitment [225].…”
Section: Other Oxpls Derivatives: Lysophospholipidsmentioning
confidence: 99%
“…IL-1β augments transcription of the IL-8 gene (Ho et al 2007), and IL-8 gene expression has been shown to be induced by tumor necrosis factor (Wang et al 1991) and lysophosphatidylcholine (Aiyar et al 2007), which is thought to play a major role in the proinflammatory effects of oxidized low density lipoprotein (oxLDL) (Steinberg et al 1989). However, mechanisms behind these molecules to up-regulate IL-8 have not yet been described.…”
Section: Introductionmentioning
confidence: 99%